Education in Learning Religious Education in College Education in Palopo City - Yunus Yunus (Journal on Education, 2021)
Cultivating awareness of the multicultural dimension in a plural and multicultural society through education is urgent because education is a potential entry point to instill an appreciation for diversity due to ethnicity, religion, gender, and family economic background and others. college student. This study aims to describe the cultural values ​​of Bugis in Islamic education that develop in universities in Palopo City. In research using qualitative. The culture of siri 'in religious learning from students' attitude of discipline and responsibility. Discipline and student responsibility to maintain self-esteem and dignity of students which are a reflection of the culture of siri 'which functions as the spirit of students in the value education process. The concept of siri learning in education provides respectful values ​​such as Sipakatau (giving information), Sipakalebbi (Mutual Respect), Sipakaingge (Reminding each other), Sipakatou (Sharing). Bugis culture has a sense of love and affection for others which is shown by proverbs such as Mali siparappe, rebba sipatokkong, malilu sipakainge (other people are taken away, helped, some fall, are helped to wake up, others come out of the norm to be reminded / repent). Bugis people are fellow human beings, let alone fellow humans. So that Bugis cultural education is in line with the values ​​of pluralism that grow and develop in Indonesia.